Literature Study: Risk Factors for Post Partum Blues - satriawati, Arisda candra; Aulia, Aulia; Sari, Puput Kurnia; Andrian, Maulana Widi (Fakultas Ilmu Kesehatan, 2023)
Post partum blues is an emotional disorder in postpartum mothers that is rarely detected and has become a problem in recent decades. Common symptoms are usually irritability, irritability, easy crying, sleep disorders, eating disorders and others. Mothers who havebeen syndicated to experience the post partum blues should be identified and immediately get strong treatment. Post partum blues that are not handled properly can pose a risk to both the mother and the baby. This study aims to analyze several risk factors for postpartum blues, as a preventive effort to detect early and can be immediately provided adequate services. The method of writing a literature study is the narrative research method of literature studies that describe the risk factors for the occurrence of postpartum blues. In this study there are factors that influence the occurrence of postpartum blues, namely umur, economic status, husband support, education, employment, and type of childbirth. The conclusion of the literature studied is that there are risk factors that can affect the occurrence of postpartum blues, including age, economic status, husband support, education, occupation, and type of childbirth. The impact of the post partum blues in addition to the impact on the mother also has an impact on thebaby and his family. Post partum blues can be prevented by routine pregnancy checks, good childbirth preparation, adequate family support, mature marriage age, mental readiness of mothers and husbands, adaptability to a good environment, emotional coping, adequate health worker support and seeking health information from trusted sources.